1868. Successful Use of Telemedicine vs. On-site Infectious Diseases Consultation After Implementation of a System-Wide Antimicrobial Stewardship-Led Staphylococcus aureus Bacteremia Care Bundle. (26th November 2018) - Isip, Jacqueline; Medaris, Leigh Ann; McCurdy, Lewis; Kowalkowski, Marc; Fischer, Kristin; Onsrud, Jennifer; Davidson, Lisa
Abstract: Background: Telemedicine (TM) programs have been effectively implemented to deliver specialty care through virtual platforms to overcome geographic and resource constraints. Yet, few data exist to describe outcomes associated with TM-based management of patients with infectious diseases (ID). The purpose of this study was to compare adherence and other outcomes associated with TM and on-site (SOC) ID consultation (IDC) implementation strategies of an antimicrobial stewardship (ASP)-led S. aureus bacteremia (SAB) bundle. Methods: We launched an SAB bundle at 10 acute care hospitals in the metro Charlotte, NC area in September 2016 for adult patients admitted with SAB and conducted a retrospective cohort study using data collected through 2017. Bundle components included (1) mandatory IDC, (2) appropriate antibiotics within 24 hours of S. aureus speciation, (3) repeat blood cultures at least every 72 hours until clearance, (4) obtainment of an echocardiogram, and (5) appropriate duration of intravenous antibiotic therapy based on SAB severity. ASP facilitated bundle initiation and assisted with compliance for all patients. The primary outcome was bundle adherence. Secondary outcomes included time to culture clearance and persistent SAB (i.e., positive blood cultures for >7 days). We used Wilcoxon rank-sum and chi-squared tests to compare outcomes. Results: We evaluated 872 patients with SAB during the study interval. After excluding 126 patients (prematurely discharged or died/transitioned to comfort care within 48 hours of S. aureus speciation), we analyzed 583 SOC and 163 TM group patients. There were no differences observed in overall SAB bundle adherence (SOC 86% vs. TM 88%, P = 0.52), or its individual components. No differences were found in time to culture clearance (median days: SOC = 2.9 vs. TM = 2.8, P = 0.96) and persistent SAB (SOC 11% vs. TM 11%, P = 0.77). Conclusion: Our findings provide preliminary evidence to support TM-based strategies for IDC and ASP-led care bundles in resource-limited settings. Future analyses will compare mortality and hospital readmission outcomes. Disclosures: All authors: No reported disclosures.